Hardness Examination of ZA 27/MoS2 Hybrid metal matrix composite using Vicker and Brinell hardness test - Mohamed Kafeel Delvi , K Mohamed kaleemulla , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
ZA 27 is a family group of Zinc Aluminium alloy which possess excellent mechanical and tribological properties. In present work, Vicker and Brinell hardness examination of ZA27 is carried out after reinforcing it with MoS2 particle in proportion of 0%, 1% and 2% using the stir casting method. Casted material is machined and turned surface that can be placed in a hardness testing machine. Before placing in a machine, flattened surfaces of both reinforced and unreinforced materials are mirror polished using sandpaper. Examination of both Vicker and Brinell hardness test results is carried out for both unreinforced and reinforced ZA 27/MoS2 hybrid metal matrix composites. Result revealed that as the percentage of MoS2 increased, the hardness of ZA 27 alloy also increased but a different range of result observed for Brinell and Vickers testing machine which is discussed in this paper.